Operational model of management system management art culture of future labor teachers - Bohatyrоva H.A. (Pedagogy of Higher and Secondary Education, 2006)
In article ways of realization of adaptive management are opened by system of fbrmunan of art culture of the future teachers of work. Which is impossible without interaction all participants of pedagogical process. The author develops organizational model of management which is capable to provide productivity offunctioning ofthe given system.